Implementasi Penilaian HOTS dan Media Pembelajaran pada Mata Pembelajaran Al-Qur’an Hadis di MAS Azzanjabil Bireuen - Abdullah, Salahuddin; Yusnaini, Yusnaini (Pase: Journal of Contemporary Islamic Education, 2023)
Assessment based on Higher Order Thinking Skills (HOTS) and the use of instructional media are two essential components of 21st-century learning. In the context of the Al-Qur’an Hadis subject, both play a vital role in fostering students’ critical, creative, and contextual thinking abilities. However, the implementation of HOTS and instructional media at the Madrasah Aliyah still faces various challenges, particularly in terms of teachers’ understanding and classroom practices. This study employs a qualitative approach using a case study method. Data were collected through in-depth interviews, participatory observation, and document analysis involving Al-Qur’an Hadis teachers at MAS Azzanjabil Bireuen. Thematic analysis was conducted using descriptive-analytical techniques, and data validity was strengthened through source and method triangulation. The findings indicate that teachers have a reasonably good understanding of HOTS and instructional media. They can articulate the principles of HOTS-based assessment and utilize media such as YouTube, laptops, and projectors in their teaching practices. However, the implementation of HOTS questions remains inconsistent due to concerns about student workload and technical limitations. HOTS-based assessment and instructional media should not be viewed merely as technical tools, but as pedagogical strategies that enhance the quality of learning and support teacher professionalism. This study offers both conceptual and practical contributions to the development of Al-Qur’an Hadis instruction that aligns with the demands of 21st-century education.